Development and Characterization of Organic Electronic Scaffolds for Bone Tissue Engineering. Issue 12 (25th April 2016) - Iandolo, Donata; Ravichandran, Akhilandeshwari; Liu, Xianjie; Wen, Feng; Chan, Jerry K. Y.; Berggren, Magnus; Teoh, Swee‐Hin; Simon, Daniel T.
Abstract : Bones have been shown to exhibit piezoelectric properties, generating electrical potential upon mechanical deformation and responding to electrical stimulation with the generation of mechanical stress. Thus, the effects of electrical stimulation on bone tissue engineering have been extensively studied. However, in bone regeneration applications, only few studies have focused on the use of electroactive 3D biodegradable scaffolds at the interphase with stem cells. Here a method is described to combine the bone regeneration capabilities of 3D‐printed macroporous medical grade polycaprolactone (PCL) scaffolds with the electrical and electrochemical capabilities of the conducting polymer poly(3, 4‐ethylenedioxythiophene) (PEDOT). PCL scaffolds have been highly effective in vivo as bone regeneration grafts, and PEDOT is a leading material in the field of organic bioelectronics, due to its stability, conformability, and biocompatibility. A protocol is reported for scaffolds functionalization with PEDOT, using vapor‐phase polymerization, resulting in a conformal conducting layer. Scaffolds' porosity and mechanical stability, important for in vivo bone regeneration applications, are retained. Human fetal mesenchymal stem cells proliferation is assessed on the functionalized scaffolds, showing the cytocompatibility of the polymeric coating. Altogether, these results show the feasibility of the proposed approach to obtain electroactive scaffolds for electrical stimulation of stem cells for regenerative medicine. Abstract : PEDOT‐coated 3D macroporous scaffolds are developed as active substrates for mesenchymal stem cell culture . The conducting polymer PEDOT:tosylate is deposited on medical‐grade polycaprolactone scaffolds via vapor phase polymerization. This results in a continuous conformal layer, and electrically and electrochemically active scaffolds. The mechanical strength of the functionalized scaffolds can be preserved, and they are shown to promote stem cell proliferation.